Overhauling kit for wdg4/wdp4 locomotive engine governor [Tender documents : T25727950] (MENA Report, 2015)
Instructions/Remarks: Please Read This As Bulletin Tender Instead Of Open Tender. Tender Document Cost Shown As Rs.500/- And Emd Rs.10/- Is Not Applicable And Need Not Be Paid.All Vendors Register With Central Railways For The Trade Group 1029 Are Eligible To Participate, However, Purchaser Reserve The Right To Consider Offers Of The Firms Registered For Other Than Tender Trade Group Subject To Documentary Support Submitted By Them Uploading Of I.E.